Home / lecture hall automation - Ammar, Adzman (2009)
Nowdays, automation system becomes the best solution to overcome human problem which is always forget to switch off the electrical appliances. As we know, there are a lot of types of the automation system which is to expensive and difficult to use.For that reason, an automation system at low cost is built where, user can also program the automated system by their own. The purpose of this project is to design an automation system that can be used to switch ON and OFF the electrical appliances automatically. This project focusing developing a automation system with ultrasonic motion detector which is controlled by programmable interface controller (PIC16F877A). This overall project is divided into two parts. The first part is concern on the hardware development where all electronic component are connected on a single board. A limit switch and ultrasonic motion detector are the input component while flourescent lamp and fan are the output component where it’s all controlled by controller circuit. The second part is base on software programming to operate the hardware structure. Program for automation system is base on PIC16F877A pic basic language. The pic basic language assemble using microcode studio software to get the hex file. The hex file loaded into PIC memory using PIC burner. The process of downloading and execute the hex file using WinPic800 Downloader. In order to achieve better automation system, the security system can be added to this project where more sensor and load can be connected to the PIC serial port. As the result, the PIC capable to control the whole operation of this automation system.